Advanced age influences the dynamic changes in circulating C-reactive protein following injury. Issue 8 (28th March 2013) - Pinato, David J; Bains, Jasmeen; Irkulla, Sashidhar; Pomroy, Josh; Ujam, Bedri; Gaze, David; Mendall, Michael A
Abstract : Background: The concentration of C-reactive protein (CRP), a biomarker of systemic inflammation, is determined by genetic, clinical and demographic factors including gender, smoking and body mass index (BMI). The influence of age on CRP dynamic changes following insult has, however, been poorly characterised. Methods: We used unilateral hernia repair as a model of standardised insult to investigate the influence of baseline demographic and clinico-pathological factors affecting the dynamic changes in CRP, interleukin (IL) 6 and tumour necrosis factor-α over a time course of 48 h following injury. Results: We derived CRP negativisation kinetics on 100 prospectively enrolled male subjects with mean age of 60.6 years (range 24–90 years) and mean BMI of 25.7 kg/m 2 (range 17.9–37 kg/m 2 ). Patients who failed to normalise CRP to<10 mg/l at 48 h (n=74) were significantly older (p<0.001), had longer surgical times (p=0.05), higher waist/hip ratio (p=0.02). Multiple regression analysis confirmed age as the only independent predictor of delayed CRP normalisation (p=0.03). Persistent CRP elevation was associated with higher peak CRP values (p<0.001), higher IL-6 concentrations at 24 (p=0.01) and 48 h (p=0.03). Conclusions: CRP decline following insult is delayed in elderly patients as a result of unopposed IL-6 release. Age should be routinely incorporated in the assessment of CRP response to avoid misinterpretation of age-related delay in CRP clearance with ongoing systemic inflammation.